An efficient asynchronous spatial division multiplexing router for network-on-chip on the hardware platform - Renu siddagangappa; Nayana Dunthur Krishnagowda; Deepthi Tumkur Srinivas Murthy (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The quasi-delay-insensitive (QDI) based asynchronous network-on-chip (ANoC) has several advantages over clock-based synchronous network-on-chips (NoCs). The asynchronous router uses a virtual channel (VC) as a primary flow-control mechanism however, the spatial division multiplexing (SDM) based mechanism performs better over input traffics over VC. This manuscript uses an asynchronous spatial division multiplexing (ASDM) based router for NoC architecture on a field-programmable gate array (FPGA) platform. The ASDM router is configurable to different bandwidths and VCs. The ASDM router mainly contains input-output (I/O) buffers, a switching allocator, and a crossbar unit. The 4-phase 1-of-4 dual-rail protocol is used to construct the I/O buffers. The performance of the ASDM router is analyzed in terms of lower urinary tract symptoms (LUTs) (chip area), delay, latency, and throughput parameters. The work is implemented using Verilog-HDL with Xilinx ISE 14.7 on artix-7 FPGA. The ASDM router achieves % chip area and obtains 0.8 ns of latency with a throughput of 800 Mfps. The proposed router is compared with existing asynchronous approaches with improved latency and throughput metrics.